THE RELATIONSHIP BETWEEN LEVEL OF KNOWLEDGE AND COMMUNITY ATTITUDES ABOUT TRADITIONAL MEDICINE IN MAJASEM HAMLET, MADUREJO SUB-DISTRICT, PRAMBANAN SLEMAN SUB-DISTRICT - Nur Selfia Kurniasari; Qarriy Aina Urfiyya (STIKES Telogorejo Semarang, 2024)
Abstract: Preface : The use of traditional medicine in Indonesia continues to increase. In the Special Region of Yogyakarta, the use of traditional medicines is quite high, reaching 58.1% in 2013. However, the community's knowledge of traditional medicines is still low and limited to herbal medicine. Purpose : To describe the level of knowledge, attitudes and the relationship between knowledge and attitudes towards traditional medicines. Method : This research using analytic observational design with a cross sectional technic. The sampling technique used purposive sampling on 70 respondents in Majasem Hamlet, Madurejo Village, Prambanan District, Sleman. The data observed included patient characteristics (age, gender, education and occupation), level of knowledge, attitudes, and the relationship between the level of knowledge and attitudes towards traditional medicines, using the Kruskal-Wallis statistical test. Result : In this study, there were more female respondents than male respondents, namely 62%. The most age was the age group of 17-25 years (31%). Meanwhile, the most levels of education and occupation were housewives (34%) and high school (61%). The majority of the community's level of knowledge about traditional medicine was in the sufficient category (50%), the attitude towards the use of traditional medicine was in the majority in the good category (84.2%). The Kruskal-Wallis test results obtained a significance value of 0.005 <0.05. Conclusion : The level of community knowledge about traditional medicine is in the good (28.5%), intermediate (50%), and poor (21.5%) categories. Attitudes to the use of traditional medicine were in the good (84.2%), intermediate (14.3%) and bad (1.5%) categories, and there was a relationship between the level of knowledge and attitudes towards traditional medicine. Keywords: traditional medicine, level of knowledge, attitude